1997
DOI: 10.1177/019262339702500205
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrastructural Histochemistry and Light Microscopy Study of the Early Development of Renal Proximal Tubular Vacuolation after a Single Administration of the Contrast Enhancement Medium "Iotrolan"

Abstract: The time course of contrast media (CM)-induced renal proximal tubular vacuolation was investigated in rats by light microscopy, transmission electron microscopy (TEM), and ultrastructural histochemistry for acid phosphate activity. Young adult male rats were treated with a single dose of 3.0 g I/kg Iotrolan (Isovist 300 mg I/ml) and sacrificed at 0 min, 5-min, 15-min, 15-min, 2-hr, and 24-hr intervals. Light microscopy of vibratome sections of freshly excised tissue of cryostat and paraffin sections was also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Therefore, rabbits offer more reliable model; however, rabbit facilities are not as common as mouse or rat facilities as rabbits are much more expensive to keep. Although tubular epithelial cell vacuolization was described in rats following a single injection of RCM without additional kidney pathology [72, 90, 91], vacuolization alone is not specific enough as a sole end-point to demonstrate CI-AKI. Although functional and histological damage was absent, molecular changes (increased adenosine receptor expressions) were induced by a single iodixanol injection even in mice [92].…”
Section: Rodent Models Of Ci-akimentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, rabbits offer more reliable model; however, rabbit facilities are not as common as mouse or rat facilities as rabbits are much more expensive to keep. Although tubular epithelial cell vacuolization was described in rats following a single injection of RCM without additional kidney pathology [72, 90, 91], vacuolization alone is not specific enough as a sole end-point to demonstrate CI-AKI. Although functional and histological damage was absent, molecular changes (increased adenosine receptor expressions) were induced by a single iodixanol injection even in mice [92].…”
Section: Rodent Models Of Ci-akimentioning
confidence: 99%
“…Tubular vacuolization is commonly interpreted as a sign of drug toxicity [107]. A single injection of RCM to intact rats induced tubular vacuolization in the absence of other kidney pathologies [72, 90, 91]. Ultrastructural studies of these kidneys suggested that the vacuoles were membrane-bound lysosomes [42, 65, 90].…”
Section: Characteristic Histopathological Changes In Ci-akimentioning
confidence: 99%
See 1 more Smart Citation
“…74,240À242 Ultrastructural study has shown that after administration of sucrose solutions renal tubular vacuoles are large, pale, surrounded by a simple membrane and show acid phosphatase activity indicating their lysosomal nature. 246 Although nephropathy induced by iodinated contrast medium remains a clinically important complication of their use in patients with compromised renal function, dosing normal healthy animals with clinically relevant doses produces only minor changes to renal blood flow, not sufficient to cause persistent derangement of renal function. While these vacuoles induced by sugar solutions and dextrans may be considered mild reversible lesions, renal failure may result from infusions of certain dextrans of particular molecular weight.…”
Section: Tubular Vacuolationmentioning
confidence: 99%
“…All water‐soluble, nephrotropic, iodinated CM exert direct toxic effects on renal epithelial cells and might produce contrast‐induced renal medullary ischemia 17,18 . Direct cytotoxic effects in the form of cytoplasmic vacuolization and lysosomal alteration in the proximal convoluted tubular cells and in the inner cortex of the kidneys have been demonstrated following exposure to a variety of iodinated CM 19–21 . Studies in animals have suggested that oxidant‐mediated injury might arise due to an enhanced production of oxygen‐free radicals concomitant with a reduction in the activity of the antioxidant enzymes catalase and superoxide dismutase in the renal cortex 22 .…”
Section: Pathogenesismentioning
confidence: 99%